Participation And Role Ulama In Eradication Of Moneylender In Aceh - Hamsa, Amrizal; Ramly, Arroyyan (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to find answers regarding the role and participation of Islamic religious scholars in eradicating loan sharks in Aceh. The actions of moneylenders in providing loans with high returns make it difficult for people to repay loans. in this case the researcher assumes that the participation of the ulema as a social elite as a pesantren leader is only to provide religious understanding to the community and provide legal fatwas. questions from researchers how are the participation of ulama in eradicating loan sharks in Aceh and what are the patterns of Islamic scholars in providing understanding related to eradicating moneylenders in Aceh. Respondents in this study were 12 people including Islamic scholars and the community. with in-depth interview method. research analysis using descriptive method by describing the phenomena that occur in the field. The research results obtained show that the participation of the Ulama is very high in eradicating moneylenders in Aceh, such as the strategic steps that have been taken to provide understanding to the community to avoid rent-seeking practices. then issued a fatwa regarding the prohibition of loan sharks and built a joint movement with the government to issue regulations against moneylender eradication in Aceh.